INNOVATION IN EDUCATION FUND MANAGEMENT: A STUDY OF THE APPLICATION OF BLOCKCHAIN TECHNOLOGY FOR TRANSPARENCY AND EFFICIENCY - Yudhianto, Kresna Agung; Siregar, Juarni; Hajar, Baiq Siti (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This research aims to explore the potential for applying blockchain technology to increase transparency and efficiency in managing education funds in schools. The research method used is a qualitative approach, through interviews with education managers and analysis of field findings. The research results show that blockchain technology has great potential in increasing transparency, accountability and efficiency in the management of education funds. By recording every transaction openly and irreversibly in the blockchain, schools can increase the level of transparency and enable real-time monitoring of funds. The use of smart contracts can also automate most administrative processes, reducing the risk of human error and saving time and costs. Recommendations for future research are to further explore the application of blockchain technology in broader educational contexts, as well as deepen understanding of the technical challenges, security, and associated social and economic impacts. By conducting further research in this area, we can expand our knowledge of the potential of blockchain technology in improving the overall quality of education.